Identification and definition of long-stay mental hospital population. Issue 5998 (20th December 1975) - Fottrell, E; Peermohamed, R; Kothari, R
Abstract : In a study to identify and define a central group of long-stay psychiatric patients who are resistant to discharge 422 were found who had been in hospital for eight to 23 years. These "problem" patients represented 40% of all long-stay patients. The total number of years that they had spent in hospital was nearly double that of the remaining patients. They were mostly unvisited, unoccupied, and single, and most were suffering from schizophrenia or organic psychosis. Half were in a good or reasonably good state of mental health, and three-quarters were in a good or reasonably good state of physical health. The findings have implications for the rehabilitation and treatment of these patients and also for the provision of community aftercare facilities.